2014
DOI: 10.1073/pnas.1323499111
|View full text |Cite
|
Sign up to set email alerts
|

Limiting glutamate transmission in a Vglut2 -expressing subpopulation of the subthalamic nucleus is sufficient to cause hyperlocomotion

Abstract: The subthalamic nucleus (STN) is a key area of the basal ganglia circuitry regulating movement. We identified a subpopulation of neurons within this structure that coexpresses Vglut2 and Pitx2, and by conditional targeting of this subpopulation we reduced Vglut2 expression levels in the STN by 40%, leaving Pitx2 expression intact. This reduction diminished, yet did not eliminate, glutamatergic transmission in the substantia nigra pars reticulata and entopeduncular nucleus, two major targets of the STN. The kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 41 publications
10
62
1
Order By: Relevance
“…3I). These findings are in agreement with a recent study, where impaired neurotransmission in the STN was shown to induce locomotion in the presence of normal motor coordination and gait29. Taken together, this suggests that Foxa1 deletion from the STN is at the roots of the observed hyperlocomotion phenotype, whereas midbrain motor programs are not affected by the ablation of Foxa1, probably due to the continued presence of Foxa2.…”
Section: Resultssupporting
confidence: 93%
“…3I). These findings are in agreement with a recent study, where impaired neurotransmission in the STN was shown to induce locomotion in the presence of normal motor coordination and gait29. Taken together, this suggests that Foxa1 deletion from the STN is at the roots of the observed hyperlocomotion phenotype, whereas midbrain motor programs are not affected by the ablation of Foxa1, probably due to the continued presence of Foxa2.…”
Section: Resultssupporting
confidence: 93%
“…; Schweizer et al . ) of both sexes. All experiments were performed in strict accordance with the Swedish regulation guidelines (Animal Welfare Act SFS 1998:56) and European Union legislation (Convention ETS123 and Directive 2010/63/EU).…”
Section: Methodsmentioning
confidence: 95%
“…The animals had ad libitum access to food (R36, Labfor; Lactamin, Vadstena, Sweden) and water. Animals used in this study were Pitx2-cre tg/wt mice (Targeted allele MGI:2445429; mice obtainable from MMRRC: RRID: MMRRC_000126-UCD) (Skidmore et al 2008;Schweizer et al 2014) of both sexes. All experiments were performed in strict accordance with the Swedish regulation guidelines (Animal Welfare Act SFS 1998:56) and European Union legislation (Convention ETS123 and Directive 2010/63/EU).…”
Section: Ethical Statementmentioning
confidence: 99%
See 2 more Smart Citations